ANALISIS MANAJEMEN PEMASARAN KREDIT LUNAK BERBASIS FINANCIAL TECHNOLOGY BUMDES RIDAN - Hasan, Samsurijal; Farhas, Risqon Jamil; Librianty, Nany L (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2022)
This research was motivated by the difficulty of applying for soft credit loans directly in the last two years due to the adjustment of the digital-based loan mechanism in the village-owned business entity Ridan Permai. This study aims to analyze the marketing management of soft credit based on financial technology which is carried out by a business entity owned by the village of Ridan Permai. The research method used is a qualitative descriptive method. The number of respondents in this study amounted to 20 people. The number of respondents represents only one neighborhood unit. The results show that the marketing management of soft credit based on financial technology needs more companions and more intense socialization. The contribution of the results of this research provides additional knowledge and skills of the community when using financial applications when applying for soft loans to develop their respective businesses. have to queue when applying for a loan.